Evidence for hypomotility in non-ulcer dyspepsia: a prospective multifactorial study. Issue 3 (March 1991) - Waldron, B; Cullen, P T; Kumar, R; Smith, D; Jankowski, J; Hopwood, D; Sutton, D; Kennedy, N; Campbell, F C
Abstract : A prospective multifactorial study of symptoms and disturbance of gastrointestinal function has been undertaken in 50 patients with non-ulcer dyspepsia. Objective tests including solid meal gastric emptying studies, gastric acid secretion, E-HIDA scintiscan for enterogastric bile reflux, and hydrogen breath studies were carried out in all patients and validated against control data. Gastroscopy and biopsy were carried out in non-ulcer dyspepsia patients only. Non-ulcer dyspepsia patients were categorised on the basis of predominant symptoms as: dysmotility-like dyspepsia (n = 22); essential dyspepsia (n = 14), gastro-oesophageal reflux-like dyspepsia (n = 11); and ulcer-like dyspepsia (n = 3). In the total non-ulcer dyspepsia population, solid meal gastric emptying was delayed (T50 mean (SEM) = 102 (6) minutes (patients) v 64 (6) minutes (controls), (p less than 0.01) and high incidences of gastritis (n = 26) and Helicobacter pyloridis infection (n = 18) were found. An inverse correlation was observed between solid meal gastric emptying and fasting peak acid output (r = -0.4; p less than 0.01). Indeed gastric emptying was particularly prolonged in eight patients (T50 mean (SEM) = 139 (15) minutes) with hypochlorhydria. In the non-ulcer dyspepsia population oral to caecal transit time of a solid meal was delayed (mean SEM = 302 (14) minutes (patients) v 244 (12) minutes (controls) (p less than 0.01]. Seven patients had a dual peak of breath hydrogen suggestive of small bowel bacterial overgrowth. No association was observed between symptoms and any of the objective abnormalities. This multifactorial study has shown that hypomotility, including gastroparesis and delayed small bowel transit, is common in non-ulcer dyspepsia and may be related to other disorders of gastrointestinal function. No relation between symptoms and disorders of function, however, has been shown.